Prevalence of MCI and Dementia Prior to Incarceration. (17th December 2021) - Kuffel, Randall; Byers, Amy; Williams, Brie; Fortinsky, Richard; Boscardin, John; Li, Yixia; Barry, Lisa
Abstract: As the number of older, incarcerated persons increases, prevalence of dementia and mild cognitive impairment (MCI) in this population will likely grow, with implications for healthcare costs and advance care planning within the prison setting. This study is the first to determine the prevalence of dementia or MCI in later-life adults prior to incarceration. We leveraged a national cohort of Veterans aged 50+ whose most recent incarceration was ≤10 years in length and who were released between 10/1/2012 and 9/30/2018 (N=17, 962). We linked VA and CMS healthcare records to determine diagnosis of dementia or MCI within 3 years prior to incarceration. The overall sample had a mean age of 62.4 (±7.6) years at the start of their incarceration, were largely male (97%), and were 65% White and 30% Black. Before incarceration, 445 (2.5%) and 152 (0.8%) Veterans were diagnosed with dementia and MCI, respectively. Compared to those without a diagnosis of dementia or MCI prior to incarceration, those with dementia or MCI were older at incarceration start (66.1 [±8.3] vs. 62.3 [±7.9]), had more chronic medical conditions (4.0 [±2.2] vs. 2.2 [±1.9]), were more likely to experience homelessness (21.6% vs. 9.1%), have a TBI (24.5% vs. 9.1%), and have serious mental illness (81.7% vs. 49.1%). All comparisons were significant (p<.001). Our findings indicate that later-life adults with dementia or MCI are being incarcerated. Improved understanding of pathways linking cognitive impairment to later-life incarceration is needed to both prevent unnecessary incarceration and to help provide appropriate healthcare for this vulnerable group.